2015
DOI: 10.4314/ijmu.v10i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension prevalence and awareness among a health workforce in Nigeria

Abstract: ABSTRACT:Hypertension is now being widely reported in Africa and it is a major factor in the high mortality of adults in sub-Saharan Africa. Unfortunately hypertension is often unnoticed and undiagnosed because it is usually asymptomatic. As such, many people with hypertension are unaware of their condition. The aim of the study was to determine the prevalence of hypertension and related risk factors and to assess the level of awareness of hypertensive status among the health workers. This study is a descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…This buttresses the fact that hypertension is a silent killer which shows no symptom until there is manifestation of cardiovascular disorders [24]. Prevalence of hypertension among the health workers in this study is similar to what Owolabi et al, [25] reported among the health workforce in Baptist Medical Hospital, Ogbomoso. But, hypertension in this study is lower than 36.6% which Ojomu et al, [19] reported among health workers in the same study location six years earlier.…”
Section: Discussionsupporting
confidence: 88%
“…This buttresses the fact that hypertension is a silent killer which shows no symptom until there is manifestation of cardiovascular disorders [24]. Prevalence of hypertension among the health workers in this study is similar to what Owolabi et al, [25] reported among the health workforce in Baptist Medical Hospital, Ogbomoso. But, hypertension in this study is lower than 36.6% which Ojomu et al, [19] reported among health workers in the same study location six years earlier.…”
Section: Discussionsupporting
confidence: 88%
“…However, the rate is lower than the 17.5% to 37.5% recorded among health workers in a systematic review of hypertension prevalence in West Africa as well as the 34% prevalence reported among College of Health Sciences employees in a Ghanaian University [ 17 , 29 ]. Moreover, prevalence rates higher than that of the current study have also been reported in Nigerians [ 30 ], Indians [ 3 ], and Europeans [ 5 ]. Of particular interest in the current study is the high rate of prehypertension observed among this apparently healthy Ghanaian health work professionals.…”
Section: Discussioncontrasting
confidence: 58%
“…The overall prevalence of undiagnosed hypertension (50%) recorded among employees in this study is high. This prevalence is almost similar to the 52% reported among a working population in South Africa [18], but higher compared to prevalence reported among workforces in other countries, such as Brazil (32%) [49] and Nigeria (20.1%) [50]. A South African study on hypertension among primary health care professional nurses has reported that 41% of the health care workers were unaware of their hypertensive status [18].…”
Section: Discussionsupporting
confidence: 74%